An Insight Into Pentatricopeptide-Mediated Chloroplast Necrosis via microRNA395a During Rhizoctonia solani Infection - Srikakulam, Nagesh; Guria, Ashirbad; Karanthamalai, Jeyalakshmi; Murugesan, Vidya; Krishnan, Vignesh; Sundaramoorthy, Kasthuri; Saha, Shakkhar; Singh, Rudransh; Victorathisayam, Thiveyarajan; Rajapriya, Veeraputhiran; Sridevi, Ganapathi; Pandi, Gopal (Frontiers in Genetics, 2022)
Sheath blight (ShB) disease, caused by Rhizoctonia solani, is one of the major biotic stress-oriented disease that adversely affects the rice productivity worldwide. However, the regulatory mechanisms are not yet understood comprehensively. In the current study, we had investigated the potential roles of miRNAs in economically important indica rice variety Pusa Basmati-1 upon R. solani infection by carrying out in-depth, high throughput small RNA sequencing with a total data size of 435 million paired end raw reads from rice leaf RNA samples collected at different time points. Detailed data analysis revealed a total of 468 known mature miRNAs and 747 putative novel miRNAs across all the libraries. Target prediction, gene ontology functional analysis of these miRNAs were found to be unravelling various cellular, molecular and biological functions by targeting various plant defence related genes. Quantitative reverse transcription polymerase chain reaction (qRT-PCR) was performed to validate the miRNAs and their putative targets genes. Out of the selected miRNA specific putative target genes, miR395a binding and its cleavage site on pentatricopeptide were determined by 5’ RACE-PCR. It might be possible that R. solani instigated chloroplast degradation by modulating the pentatricopeptide which led to increased susceptibility to fungal infection.